2015
DOI: 10.1007/s00134-014-3615-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of neutropenic patients admitted to the intensive care unit

Abstract: Hospital survival was closely associated with younger age and neutropenic enterocolitis. Conversely, need for conventional MV, for renal replacement therapy, and allogeneic hematopoietic stem cell transplantation (HSCT) were associated with poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
2
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 44 publications
(11 reference statements)
6
46
2
10
Order By: Relevance
“…That the proportion of hematological patients increased over time, and that their mortality decreased over time confirms recent findings [17]. Interestingly, in this study, in which mortality was 47 % (41-54 %), neutropenia was not a predictor of mortality after adjustment of confounders, a result in line with the paper from Mokart et al reporting hospital mortality of 45 % in a cohort of 289 patients with neutropenia [18]. Lastly, a large multicenter study of 6373 HIV-infected patients admitted in 34 ICUs over a 12-year study period confirmed the shift for improved outcomes and changing the use of ICU for HIV patients.…”
Section: Discussionsupporting
confidence: 92%
“…That the proportion of hematological patients increased over time, and that their mortality decreased over time confirms recent findings [17]. Interestingly, in this study, in which mortality was 47 % (41-54 %), neutropenia was not a predictor of mortality after adjustment of confounders, a result in line with the paper from Mokart et al reporting hospital mortality of 45 % in a cohort of 289 patients with neutropenia [18]. Lastly, a large multicenter study of 6373 HIV-infected patients admitted in 34 ICUs over a 12-year study period confirmed the shift for improved outcomes and changing the use of ICU for HIV patients.…”
Section: Discussionsupporting
confidence: 92%
“…Reasons for ICU admission were recorded based on the main symptoms at ICU admission [21]. Acute respiratory failure was defined as previously reported [22, 23] and neutropenia as a neutrophil count < 500/mm 3 [24]. Prespecified criteria were applied to define the causes of pulmonary involvement; [5] for possible or probable IA, the most recent definitions were used [1].…”
Section: Methodsmentioning
confidence: 99%
“…Beyond usual risk factors of poor prognosis (older age, organ failure, sepsis, allogeneic stem cell transplantation), this study identified neutropenic enterocolitis as a factor independently associated with survival. In addition, in a case-control analysis, the authors failed to demonstrate any prognostic impact of neutropenia, confirming that neutropenia per se should probably not be used for triage of cancer patients [3]. Future studies may, however, be needed in this field, in particular aimed at differentiating mechanisms of neutropenia, taking into account functional neutropenia along with associated immune defects.…”
Section: Epidemiology and Outcomesmentioning
confidence: 96%
“…Mokart et al assessed outcomes in neutropenic critically ill cancer patients [3]. Beyond usual risk factors of poor prognosis (older age, organ failure, sepsis, allogeneic stem cell transplantation), this study identified neutropenic enterocolitis as a factor independently associated with survival.…”
Section: Epidemiology and Outcomesmentioning
confidence: 98%